Sebuah Estimasi Fungsi Produksi dan Efisiensi Teknis Usaha Tani Bawang merah - Muhammad Fajar; Oktya Putri Gitaningtyas; Muhammad Muhtoni; Purwaning Dhahari (Mathematics Department, Faculty of Science and Technology, UIN Sunan Ampel Surabaya, 2019)
Shallot is one of the potential horticultural commodities. The purpose of this study is to estimate the production function and efficiency of shallot farming. The method used in the study is the estimation of production functions using stochastic frontier. The data used in this study were shallot production (kg), harvested area (m2), labor used (HOK), use of seeds (kg), fertilizer (kg), pesticides used (kg), sourced from SHR2014 which conducted by the Central Statistics Agency. In the estimation process, all variables are transformed by natural logarithms. The results showed that the estimation of the function of shallot production for both the dry season and the wet season with independent variables included harvested area, labor, seeds, fertilizers, and significant pesticides in the model, so that formed model was valid for further use. The average technical efficiency of shallot farming in the dry and wet season is 0.6626 and 0.6627, respectively, which means that in general, shallot farming in Indonesia is not efficient on the technical side. That is, there are indications that the optimal processing technology of production inputs in the business has not been carried out optimally.